The Determinants of the Value of Mahr in Muslim Societies: Evidence from the Indonesian Family Life Surveys - Friantoro, Dian; Susamto, Akhmad Akbar (Jurnal Ekonomi & Studi Pembangunan, 2021)
This paper aims to analyze the factors that determine the value of mahr in Muslim societies. The analysis is based on an ordinary least squares (OLS) regression with pooled cross-section data from the last three waves of the Indonesian Family Life Surveys (IFLS). The main finding is that socioeconomic status in the forms of groom’s ownership of assets and education level matters most for the value of mahr. This finding holds for regression with full sample as well as subsamples, i.e. couples whose groom is Javanese, couples whose groom is non-Javanese, couples whose bride is Javanese and couples whose bride is non-Javanese. Socioeconomic status in the form of bride’s education level also matters for the value of mahr with some exceptions. The other finding is that perceived probability of divorce as represented by differences in the socioeconomic status of a marrying couple do not have a significant effect on the value of mahr. The effect of physical appearances in the form of bride’s height is at best not robust and subject to the sample or subsample included. These findings can be useful as a reference to make marriage decisions in the future or to evaluate the ongoing practices for possible reforms.